Influences of footstrike patterns and overground conditions on lower extremity kinematics and kinetics during running: Statistical parametric mapping analysis. - Yifang Zhuang; Wenxing Zhou; Ziwei Zeng; Shiwei Mo; Lin Wang (PLoS ONE)
This study investigated lower extremity biomechanics when running on different surfaces among runners with different footstrike patterns. Thirty rearfoot strikers (RFSs) and non-rearfoot strikers (nRFSs) ran at 3.3 m/s on a specially designed indoor track covered with three surfaces: artificial grass, synthetic rubber, and concrete. A motion capture system with ten cameras combined a force plate was used to collect marker trajectory and ground reaction force (GRF) during the running stance phase. A two-way analysis of variance with statistical parametric mapping was employed to evaluate differences in the biomechanics of the lower extremities between footstrike patterns and among running surfaces. The nRFSs exhibited significantly greater ankle inversion angles and increased inversion and internal rotation moments at midstance compared to the RFSs. Conversely, the RFSs demonstrated significantly greater knee abduction moments in late stance. Running on stiffer surfaces was associated with greater vertical GRF in late stance, as well as increased knee and hip extension moments during midstance. Furthermore, running on stiffer surfaces was associated with increased knee abduction moments, hip abduction moments, and hip external rotation moments during late stance. These findings suggested that nRFSs endure more ankle loads, while RFSs face increased knee loads. However, regardless of the footstrike pattern, runners may benefit from selecting softer surfaces to reduce the risk of injury.